2013
DOI: 10.1002/anie.201208993
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Supercapacitor Performance of MnO2 by Atomic Doping

Abstract: Electrochemical energy storage: The performance of MnO2 as a pseudo‐capacitive material was enhanced by doping electrodeposited MnO2 with physically deposited gold atoms (see picture). The resulting MnO2 electrodes showed an enhanced electronic conductivity and a remarkable stability under voltammetric cycling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(157 citation statements)
references
References 31 publications
3
154
0
Order By: Relevance
“…have been extensively investigated as electrode materials for pseudocapacitors [23][24][25][26][27][28][29]. Among them, MnO 2 nanostructures (NSs) have received considerable attention because of their high theoretical specific capacitance, environmental friendliness, low cost, and low toxicity [30,31]. MnO 2 NSs with controllable shapes and sizes have been synthesized using different growth methods [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…have been extensively investigated as electrode materials for pseudocapacitors [23][24][25][26][27][28][29]. Among them, MnO 2 nanostructures (NSs) have received considerable attention because of their high theoretical specific capacitance, environmental friendliness, low cost, and low toxicity [30,31]. MnO 2 NSs with controllable shapes and sizes have been synthesized using different growth methods [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The latter method improved the conductivity of manganese oxides and facilitated the fast transport of ions and electrons during chargeedischarge processes [5], and the pseudocapacitance of MnO 2 encapsulated within CNTs was greatly enhanced to 1250 F g À1 [9]. It was reported that doping metallic elements, such as Al, Sn and Au, was also an important way to modify manganese oxide electrodes to enhance their electrochemical performance [5,10]. Physical vapor deposition was performed to synthesize a thick Au-doped MnO 2 film with a ultrahigh specific capacitance of 626 F g À1 at a scan rate of 5 mV s À1 [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the interstitial/intercalative doping process, dopants are directly incorporated into the lattice of a nanostructure [44,45]. In contrast, the surface doping process attaches functional groups onto the defective sites at the surface or edge of the nanostructure [7,43].…”
Section: Resultsmentioning
confidence: 99%